Innovative Leadership Style for Industrial Companies - Christine Aschbacher (European Scientific Journal, ESJ, 2020)
Innovation is a very important subject for industrial companies especially in a competitive environment. As there is a lack of innovation in combination with leadership style, this paper focuses on combining these factors as inputs for leaders of tomorrow for industrial companies. Nowadays, leaders are looking for a new kind of leadership style which drives innovation in the company. Therefore, the theoretic perspective is being considered with the basic leadership styles as well as with the input of some international successful leaders of innovative companies. Furthermore, the trends of a practical orientation of a specific industrial sector serve as findings and tips for successful innovative leadership. Finally, leaders of tomorrow will adopt some solution strategies as part of their leadership styles in innovative companies. This will help to enhance the innovative power in their industrial companies.